Concise Introduction to Global Supply Chain Management - Kotabe, Masaaki (Cheltenham : Edward Elgar Publishing, 2024)
Our Elgar Concise Introductions are inspiring and considered. They explain the key principles in business and are expertly written by some of the world$1 (Bs leading scholars. The aims of the series are two-fold: to pinpoint essential concepts of business and management, and to offer insights that stimulate critical thinking.This Concise Introduction provides clear insights into the various issues involved in the global supply chain. Covering materials procurement, sourcing, and physical distribution, Masaaki Kotabe examines the global supply chain from a strategic perspective, while also addressing the sustainability concerns which arise in this arena.s
Includes index.
Keywords: Supply chain; Managing Procurrement; Physical distribution